PENERAPAN METODE MFEP DALAM MENENTUKAN SISWA INKLUSI KESULITAN BELAJAR MENGAJAR PADA MTS. NURUL HIKMAH AFD III TINJOWAN - Hasibuan, Indah Kurnia R; Dalimunthe, Ruri Ashari; Putri, Pristiyanilicia (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Inclusive students are when carrying out the teaching and learning process, the principal together with the teachers must select and determine students who deserve inclusive education in accordance with the criteria set by the Directorate of School Development. Sometimes in the process of selecting students, mistakes often occur and they are not on target, resulting in problems when determining which students are classified as inclusive students during school examinations. And the assessment of each criterion does not use a decision method, so the assessment between participants still uses predictions or estimates which can lead to subjective assessments. This results in inaccurate selection of inclusive students with learning difficulties. As information technology develops, the problem of selecting inclusive students so that they are on target according to the criteria determined by the government through the Department of Education can be overcome, one of which is by using a decision support system using the Multi Factor Evaluation Process (MFEP) method to determine inclusion of students with learning difficulties. Where with this system, it can help make it easier for Mts. Nurul Hikmah AFD III Tinjowan in selecting and determining inclusion students with learning difficulties, so that the desired results are right on target and in accordance with the established criteria.